2016
DOI: 10.1016/j.ecoleng.2016.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in riparian soils along the Han River, China: The importance of soil properties, topography and upland land use

Abstract: Riparian zones can act as an important sink for various contaminants, including heavy metals. The retention and accumulation of heavy metals in riparian soils varies spatially and is related to many local factors, such as soil properties, topography and land use. However, the relative importance of such factors in determining the heavy metal contamination of riparian soils remains unclear. In this study, we investigated the concentrations of 10 heavy metals (i.e., Ba, Cd, Co, Cr, Cu, Mn, Ni, Pb, Sr and Zn) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Riparian zones acting as aquatic-terrestrial links play a significant role in the environment by maintaining the balance between riverbank stability, water quality and aquatic biodiversity (Liu et al, 2016). Globally, riparian areas are considered as natural buffers that filter pollutants between upland regions and open waters, as well as reducing erosion at the stream bank (Ramião et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Riparian zones acting as aquatic-terrestrial links play a significant role in the environment by maintaining the balance between riverbank stability, water quality and aquatic biodiversity (Liu et al, 2016). Globally, riparian areas are considered as natural buffers that filter pollutants between upland regions and open waters, as well as reducing erosion at the stream bank (Ramião et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we observed that Pb was correlated negatively with elevation in both June ( r = − 0.41, p = 0.08) and October ( r = − 0.40, p = 0.08). Other research indicated a relationship between the decreasing trend of HM content and increases in elevation and river flow rate during the spring 68 . During the spring, the Pearson product-moment correlation coefficient demonstrated a strong ( p < 0.001) intermetal relationship in March for Pb vs. Cu ( r = 0.74), Pb vs. Zn ( r = 0.75), Ni vs. Cr ( r = 0.74), Ni vs. Cu ( r = 0.95), and Ni vs. Zn ( r = 0.80) and in May for Cd vs. Cu ( r = 0.73), Ni vs. Cr ( r = 0.90), and Ni vs. Cu ( r = 0.92) (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, the correlations of As, Cu, Zn and Co with TN and TC suggest that heavy metals were influenced by organic matter content, as it may serve as a sink for metal(loid)s [13,39]. The result shows that improving the soil organic matter contents of the soil in the form of plant and animal residues, microbial biomass and other amendments may increase the metal(loid) adsorption of the soils and decrease soil contamination [16,39].…”
Section: Discussionmentioning
confidence: 92%